Bubaak: Runtime monitoring of program verifiers - Chalupa, Marek; Henzinger, Thomas A (Tools and Algorithms for the Construction and Analysis of Systems)
The main idea behind BUBAAK is to run multiple program analyses in parallel and use runtime monitoring and enforcement to observe and control their progress in real time. The analyses send information about (un)explored states of the program and discovered invariants to a monitor. The monitor processes the received data and can force an analysis to stop the search of certain program parts (which have already been analyzed by other analyses), or to make it utilize a program invariant found by another analysis. At SV-COMP 2023, the implementation of data exchange between the monitor and the analyses was not yet completed, which is why BUBAAK only ran several analyses in parallel, without any coordination. Still, BUBAAK won the meta-category FalsificationOverall and placed very well in several other (sub)-categories of the competition.

Vamos: Middleware for best-effort third-party monitoring - Chalupa, Marek; Mühlböck, Fabian; Muroya Lei, Stefanie; Henzinger, Thomas A (Fundamental Approaches to Software Engineering)
As the complexity and criticality of software increase every year, so does the importance of run-time monitoring. Third-party monitoring, with limited knowledge of the monitored software, and best-effort monitoring, which keeps pace with the monitored software, are especially valuable, yet underexplored areas of run-time monitoring. Most existing monitoring frameworks do not support their combination because they either require access to the monitored code for instrumentation purposes or the processing of all observed events, or both. We present a middleware framework, VAMOS, for the run-time monitoring of software which is explicitly designed to support third-party and best-effort scenarios. The design goals of VAMOS are (i) efficiency (keeping pace at low overhead), (ii) flexibility (the ability to monitor black-box code through a variety of different event channels, and the connectability to monitors written in different specification languages), and (iii) ease-of-use. To achieve its goals, VAMOS combines aspects of event broker and event recognition systems with aspects of stream processing systems. We implemented a prototype toolchain for VAMOS and conducted experiments including a case study of monitoring for data races. The results indicate that VAMOS enables writing useful yet efficient monitors, is compatible with a variety of event sources and monitor specifications, and simplifies key aspects of setting up a monitoring system from scratch.

Beyond the universal law of robustness: Sharper laws for random features and neural tangent kernels - Bombari, Simone; Kiyani, Shayan; Mondelli, Marco (Proceedings of the 40th International Conference on Machine Learning)
Machine learning models are vulnerable to adversarial perturbations, and a thought-provoking paper by Bubeck and Sellke has analyzed this phenomenon through the lens of over-parameterization: interpolating smoothly the data requires significantly more parameters than simply memorizing it. However, this "universal" law provides only a necessary condition for robustness, and it is unable to discriminate between models. In this paper, we address these gaps by focusing on empirical risk minimization in two prototypical settings, namely, random features and the neural tangent kernel (NTK). We prove that, for random features, the model is not robust for any degree of over-parameterization, even when the necessary condition coming from the universal law of robustness is satisfied. In contrast, for even activations, the NTK model meets the universal lower bound, and it is robust as soon as the necessary condition on over-parameterization is fulfilled. This also addresses a conjecture in prior work by Bubeck, Li and Nagaraj. Our analysis decouples the effect of the kernel of the model from an "interaction matrix", which describes the interaction with the test data and captures the effect of the activation. Our theoretical results are corroborated by numerical evidence on both synthetic and standard datasets (MNIST, CIFAR-10).

Quantitative assessment can stabilize indirect reciprocity under imperfect information - Schmid, Laura; Ekbatani, Farbod; Hilbe, Christian; Chatterjee, Krishnendu (Nature Communications)
The field of indirect reciprocity investigates how social norms can foster cooperation when individuals continuously monitor and assess each other’s social interactions. By adhering to certain social norms, cooperating individuals can improve their reputation and, in turn, receive benefits from others. Eight social norms, known as the “leading eight," have been shown to effectively promote the evolution of cooperation as long as information is public and reliable. These norms categorize group members as either ’good’ or ’bad’. In this study, we examine a scenario where individuals instead assign nuanced reputation scores to each other, and only cooperate with those whose reputation exceeds a certain threshold. We find both analytically and through simulations that such quantitative assessments are error-correcting, thus facilitating cooperation in situations where information is private and unreliable. Moreover, our results identify four specific norms that are robust to such conditions, and may be relevant for helping to sustain cooperation in natural populations.

Uncovering the organization of neural circuits with Generalized Phase Locking Analysis - Safavi, Shervin; Panagiotaropoulos, Theofanis I.; Kapoor, Vishal; Ramirez Villegas, Juan F; Logothetis, Nikos K.; Besserve, Michel (PLoS Computational Biology)
Despite the considerable progress of in vivo neural recording techniques, inferring the biophysical mechanisms underlying large scale coordination of brain activity from neural data remains challenging. One obstacle is the difficulty to link high dimensional functional connectivity measures to mechanistic models of network activity. We address this issue by investigating spike-field coupling (SFC) measurements, which quantify the synchronization between, on the one hand, the action potentials produced by neurons, and on the other hand mesoscopic “field” signals, reflecting subthreshold activities at possibly multiple recording sites. As the number of recording sites gets large, the amount of pairwise SFC measurements becomes overwhelmingly challenging to interpret. We develop Generalized Phase Locking Analysis (GPLA) as an interpretable dimensionality reduction of this multivariate SFC. GPLA describes the dominant coupling between field activity and neural ensembles across space and frequencies. We show that GPLA features are biophysically interpretable when used in conjunction with appropriate network models, such that we can identify the influence of underlying circuit properties on these features. We demonstrate the statistical benefits and interpretability of this approach in various computational models and Utah array recordings. The results suggest that GPLA, used jointly with biophysical modeling, can help uncover the contribution of recurrent microcircuits to the spatio-temporal dynamics observed in multi-channel experimental recordings.

Pollution impact on metal and biomarker responses in intestinal cytosol of freshwater fish - Filipović Marijić, Vlatka; Krasnici, Nesrete; Valić, Damir; Kapetanović, Damir; Vardić Smrzlić, Irena; Jordanova, Maja; Rebok, Katerina; Ramani, Sheriban; Kostov, Vasil; Nastova, Rodne; Dragun, Zrinka (Environmental Science and Pollution Research)
In the present study, essential and nonessential metal content and biomarker responses were investigated in the intestine of fish collected from the areas polluted by mining. Our objective was to determine metal and biomarker levels in tissue responsible for dietary intake, which is rarely studied in water pollution research. The study was conducted in the Bregalnica River, reference location, and in the Zletovska and Kriva Rivers (the Republic of North Macedonia), which are directly influenced by the active mines Zletovo and Toranica, respectively. Biological responses were analyzed in Vardar chub (Squalius vardarensis; Karaman, 1928), using for the first time intestinal cytosol as a potentially toxic cell fraction, since metal sensitivity is mostly associated with cytosol. Cytosolic metal levels were higher in fish under the influence of mining (Tl, Li, Cs, Mo, Sr, Cd, Rb, and Cu in the Zletovska River and Cr, Pb, and Se in the Kriva River compared to the Bregalnica River in both seasons). The same trend was evident for total proteins, biomarkers of general stress, and metallothioneins, biomarkers of metal exposure, indicating cellular disturbances in the intestine, the primary site of dietary metal uptake. The association of cytosolic Cu and Cd at all locations pointed to similar pathways and homeostasis of these metallothionein-binding metals. Comparison with other indicator tissues showed that metal concentrations were higher in the intestine of fish from mining-affected areas than in the liver and gills. In general, these results indicated the importance of dietary metal pathways, and cytosolic metal fraction in assessing pollution impacts in freshwater ecosystems.

Altered childhood brain development in autism and epilepsy - Currin, Christopher; Beyer, Chad (Encyclopedia of Child and Adolescent Health)
Autism spectrum disorder (ASD) and epilepsy are frequently comorbid neurodevelopmental disorders. Extensive research has demonstrated shared pathological pathways, etiologies, and phenotypes. Many risk factors for these disorders, like genetic mutations and environmental pressures, are linked to changes in childhood brain development, which is a critical period for their manifestation. Decades of research have yielded many signatures for ASD and epilepsy, some shared and others unique or opposing. The anatomical, physiological, and behavioral correlates of these disorders are discussed in this chapter in the context of understanding shared pathological pathways. We end with important takeaways on the presentation, prevention, intervention, and policy changes for ASD and epilepsy. This chapter aims to explore the complexity of these disorders, both in etiology and phenotypes, with the further goal of appreciating the expanse of unknowns still to explore about the brain.

Research data for: A stochastic cellular automaton model of culture formation - Klausen, Frederik Ravn; Lauritsen, Asbjørn Bækgaard
We introduce a stochastic cellular automaton as a model for culture and border formation. The model can be conceptualized as a game where the expansion rate of cultures is quantified in terms of their area and perimeter in such a way that approximately round cultures get a competitive advantage. We first analyse the model with periodic boundary conditions, where we study how the model can end up in a fixed state, i.e. freezes. Then we implement the model on the European geography with mountains and rivers. We see how the model reproduces some qualitative features of European culture formation, namely that rivers and mountains are more frequently borders between cultures, mountainous regions tend to have higher cultural diversity and the central European plain has less clear cultural borders.

Boolean network sketches: A unifying framework for logical model inference - Beneš, Nikola; Brim, Luboš; Huvar, Ondřej; Pastva, Samuel; Šafránek, David (Bioinformatics)
Motivation: The problem of model inference is of fundamental importance to systems biology. Logical models (e.g. Boolean networks; BNs) represent a computationally attractive approach capable of handling large biological networks. The models are typically inferred from experimental data. However, even with a substantial amount of experimental data supported by some prior knowledge, existing inference methods often focus on a small sample of admissible candidate models only. Results: We propose Boolean network sketches as a new formal instrument for the inference of Boolean networks. A sketch integrates (typically partial) knowledge about the network’s topology and the update logic (obtained through, e.g. a biological knowledge base or a literature search), as well as further assumptions about the properties of the network’s transitions (e.g. the form of its attractor landscape), and additional restrictions on the model dynamics given by the measured experimental data. Our new BNs inference algorithm starts with an ‘initial’ sketch, which is extended by adding restrictions representing experimental data to a ‘data-informed’ sketch and subsequently computes all BNs consistent with the data-informed sketch. Our algorithm is based on a symbolic representation and coloured model-checking. Our approach is unique in its ability to cover a broad spectrum of knowledge and efficiently produce a compact representation of all inferred BNs. We evaluate the method on a non-trivial collection of real-world and simulated data.

Marked Length Spectral determination of analytic chaotic billiards with axial symmetries - De Simoi, Jacopo; Kaloshin, Vadim; Leguil, Martin (Inventiones Mathematicae)
We consider billiards obtained by removing from the plane finitely many strictly convex analytic obstacles satisfying the non-eclipse condition. The restriction of the dynamics to the set of non-escaping orbits is conjugated to a subshift, which provides a natural labeling of periodic orbits. We show that under suitable symmetry and genericity assumptions, the Marked Length Spectrum determines the geometry of the billiard table.

Salicylic acid inhibits rice endocytic protein trafficking mediated by OsPIN3t and clathrin to affect root growth - Jiang, Lihui; Yao, Baolin; Zhang, Xiaoyan; Wu, Lixia; Fu, Qijing; Zhao, Yiting; Cao, Yuxin; Zhu, Ruomeng; Lu, Xinqi; Huang, Wuying; Zhao, Jianping; Li, Kuixiu; et al. (Plant Journal)
Salicylic acid (SA) plays important roles in different aspects of plant development, including root growth, where auxin is also a major player by means of its asymmetric distribution. However, the mechanism underlying the effect of SA on the development of rice roots remains poorly understood. Here, we show that SA inhibits rice root growth by interfering with auxin transport associated with the OsPIN3t- and clathrin-mediated gene regulatory network (GRN). SA inhibits root growth as well as Brefeldin A-sensitive trafficking through a non-canonical SA signaling mechanism. Transcriptome analysis of rice seedlings treated with SA revealed that the OsPIN3t auxin transporter is at the center of a GRN involving the coat protein clathrin. The root growth and endocytic trafficking in both the pin3t and clathrin heavy chain mutants were SA insensitivity. SA inhibitory effect on the endocytosis of OsPIN3t was dependent on clathrin; however, the root growth and endocytic trafficking mediated by tyrphostin A23 (TyrA23) were independent of the pin3t mutant under SA treatment. These data reveal that SA affects rice root growth through the convergence of transcriptional and non-SA signaling mechanisms involving OsPIN3t-mediated auxin transport and clathrin-mediated trafficking as key components.

Physics-inspired machine learning of localized intensive properties - Chen, Ke; Kunkel, Christian; Cheng, Bingqing; Reuter, Karsten; Margraf, Johannes T. (Chemical Science)
Machine learning (ML) has been widely applied to chemical property prediction, most prominently for the energies and forces in molecules and materials. The strong interest in predicting energies in particular has led to a ‘local energy’-based paradigm for modern atomistic ML models, which ensures size-extensivity and a linear scaling of computational cost with system size. However, many electronic properties (such as excitation energies or ionization energies) do not necessarily scale linearly with system size and may even be spatially localized. Using size-extensive models in these cases can lead to large errors. In this work, we explore different strategies for learning intensive and localized properties, using HOMO energies in organic molecules as a representative test case. In particular, we analyze the pooling functions that atomistic neural networks use to predict molecular properties, and suggest an orbital weighted average (OWA) approach that enables the accurate prediction of orbital energies and locations.

Lamin B1 overexpression alters chromatin organization and gene expression - Kaneshiro, Jeanae M.; Capitanio, Juliana S.; Hetzer, Martin W (Nucleus)
Peripheral heterochromatin positioning depends on nuclear envelope associated proteins and repressive histone modifications. Here we show that overexpression (OE) of Lamin B1 (LmnB1) leads to the redistribution of peripheral heterochromatin into heterochromatic foci within the nucleoplasm. These changes represent a perturbation of heterochromatin binding at the nuclear periphery (NP) through a mechanism independent from altering other heterochromatin anchors or histone post-translational modifications. We further show that LmnB1 OE alters gene expression. These changes do not correlate with different levels of H3K9me3, but a significant number of the misregulated genes were likely mislocalized away from the NP upon LmnB1 OE. We also observed an enrichment of developmental processes amongst the upregulated genes. ~74% of these genes were normally repressed in our cell type, suggesting that LmnB1 OE promotes gene de-repression. This demonstrates a broader consequence of LmnB1 OE on cell fate, and highlights the importance of maintaining proper levels of LmnB1.

Nanoparticle-based semiconductor solids: From synthesis to consolidation - Calcabrini, Mariano
High-performance semiconductors rely upon precise control of heat and charge transport. This can be achieved by precisely engineering defects in polycrystalline solids. There are multiple approaches to preparing such polycrystalline semiconductors, and the transformation of solution-processed colloidal nanoparticles is appealing because colloidal nanoparticles combine low cost with structural and compositional tunability along with rich surface chemistry. However, the multiple processes from nanoparticle synthesis to the final bulk nanocomposites are very complex. They involve nanoparticle purification, post-synthetic modifications, and finally consolidation (thermal treatments and densification). All these properties dictate the final material’s composition and microstructure, ultimately affecting its functional properties. This thesis explores the synthesis, surface chemistry and consolidation of colloidal semiconductor nanoparticles into dense solids. In particular, the transformations that take place during these processes, and their effect on the material’s transport properties are evaluated.

Stochastic cellular automaton model of culture formation - Klausen, Frederik Ravn; Lauritsen, Asbjørn Bækgaard (Physical Review E)
We introduce a stochastic cellular automaton as a model for culture and border formation. The model can be conceptualized as a game where the expansion rate of cultures is quantified in terms of their area and perimeter in such a way that approximately geometrically round cultures get a competitive advantage. We first analyze the model with periodic boundary conditions, where we study how the model can end up in a fixed state, i.e., freezes. Then we implement the model on the European geography with mountains and rivers. We see how the model reproduces some qualitative features of European culture formation, namely, that rivers and mountains are more frequently borders between cultures, mountainous regions tend to have higher cultural diversity, and the central European plain has less clear cultural borders.

Cavity quantum electrooptics - Sahu, Rishabh
About a 100 years ago, we discovered that our universe is inherently noisy, that is, measuring any physical quantity with a precision beyond a certain point is not possible because of an omnipresent inherent noise. We call this - the quantum noise. Certain physical processes allow this quantum noise to get correlated in conjugate physical variables. These quantum correlations can be used to go beyond the potential of our inherently noisy universe and obtain a quantum advantage over the classical applications. Quantum noise being inherent also means that, at the fundamental level, the physical quantities are not well defined and therefore, objects can stay in multiple states at the same time. For example, the position of a particle not being well defined means that the particle is in multiple positions at the same time. About 4 decades ago, we started exploring the possibility of using objects which can be in multiple states at the same time to increase the dimensionality in computation. Thus, the field of quantum computing was born. We discovered that using quantum entanglement, a property closely related to quantum correlations, can be used to speed up computation of certain problems, such as factorisation of large numbers, faster than any known classical algorithm. Thus began the pursuit to make quantum computers a reality. Till date, we have explored quantum control over many physical systems including photons, spins, atoms, ions and even simple circuits made up of superconducting material. However, there persists one ubiquitous theme. The more readily a system interacts with an external field or matter, the more easily we can control it. But this also means that such a system can easily interact with a noisy environment and quickly lose its coherence. Consequently, such systems like electron spins need to be protected from the environment to ensure the longevity of their coherence. Other systems like nuclear spins are naturally protected as they do not interact easily with the environment. But, due to the same reason, it is harder to interact with such systems. After decades of experimentation with various systems, we are convinced that no one type of quantum system would be the best for all the quantum applications. We would need hybrid systems which are all interconnected - much like the current internet where all sorts of devices can all talk to each other - but now for quantum devices. A quantum internet. Optical photons are the best contenders to carry information for the quantum internet. They can carry quantum information cheaply and without much loss - the same reasons which has made them the backbone of our current internet. Following this direction, many systems, like trapped ions, have already demonstrated successful quantum links over a large distances using optical photons. However, some of the most promising contenders for quantum computing which are based on microwave frequencies have been left behind. This is because high energy optical photons can adversely affect fragile low-energy microwave systems. In this thesis, we present substantial progress on this missing quantum link between microwave and optics using electrooptical nonlinearities in lithium niobate. The nonlinearities are enhanced by using resonant cavities for all the involved modes leading to observation of strong direct coupling between optical and microwave frequencies. With this strong coupling we are not only able to achieve almost 100% internal conversion efficiency with low added noise, thus presenting a quantum-enabled transducer, but also we are able to observe novel effects such as cooling of a microwave mode using optics. The strong coupling regime also leads to direct observation of dynamical backaction effect between microwave and optical frequencies which are studied in detail here. Finally, we also report first observation of microwave-optics entanglement in form of two-mode squeezed vacuum squeezed 0.7dB below vacuum level. With this new bridge between microwave and optics, the microwave-based quantum technologies can finally be a part of a quantum network which is based on optical photons - putting us one step closer to a future with quantum internet.
Keywords: quantum optics; electrooptics; quantum networks; quantum communication; transduction

A non-commutative entropic optimal transport approach to quantum composite systems at positive temperature - Feliciangeli, Dario; Gerolin, Augusto; Portinale, Lorenzo (Journal of Functional Analysis)
This paper establishes new connections between many-body quantum systems, One-body Reduced Density Matrices Functional Theory (1RDMFT) and Optimal Transport (OT), by interpreting the problem of computing the ground-state energy of a finite-dimensional composite quantum system at positive temperature as a non-commutative entropy regularized Optimal Transport problem. We develop a new approach to fully characterize the dual-primal solutions in such non-commutative setting. The mathematical formalism is particularly relevant in quantum chemistry: numerical realizations of the many-electron ground-state energy can be computed via a non-commutative version of Sinkhorn algorithm. Our approach allows to prove convergence and robustness of this algorithm, which, to our best knowledge, were unknown even in the two marginal case. Our methods are based on a priori estimates in the dual problem, which we believe to be of independent interest. Finally, the above results are extended in 1RDMFT setting, where bosonic or fermionic symmetry conditions are enforced on the problem.

Computing chemical potentials of adsorbed or confined fluids - Schmid, Rochus; Cheng, Bingqing (The Journal of Chemical Physics)
The chemical potential of adsorbed or confined fluids provides insight into their unique thermodynamic properties and determines adsorption isotherms. However, it is often difficult to compute this quantity from atomistic simulations using existing statistical mechanical methods. We introduce a computational framework that utilizes static structure factors, thermodynamic integration, and free energy perturbation for calculating the absolute chemical potential of fluids. For demonstration, we apply the method to compute the adsorption isotherms of carbon dioxide in a metal-organic framework and water in carbon nanotubes.

Symmetry-broken Josephson junctions and superconducting diodes in magic-angle twisted bilayer graphene - Díez-Mérida, J.; Díez-Carlón, A.; Yang, S. Y.; Xie, Y. M.; Gao, X. J.; Senior, Jorden L; Watanabe, K.; Taniguchi, T.; Lu, X.; Higginbotham, Andrew P; Law, K. T.; Efetov, Dmitri K. (Nature Communications)
The coexistence of gate-tunable superconducting, magnetic and topological orders in magic-angle twisted bilayer graphene provides opportunities for the creation of hybrid Josephson junctions. Here we report the fabrication of gate-defined symmetry-broken Josephson junctions in magic-angle twisted bilayer graphene, where the weak link is gate-tuned close to the correlated insulator state with a moiré filling factor of υ = −2. We observe a phase-shifted and asymmetric Fraunhofer pattern with a pronounced magnetic hysteresis. Our theoretical calculations of the junction weak link—with valley polarization and orbital magnetization—explain most of these unconventional features. The effects persist up to the critical temperature of 3.5 K, with magnetic hysteresis observed below 800 mK. We show how the combination of magnetization and its current-induced magnetization switching allows us to realise a programmable zero-field superconducting diode. Our results represent a major advance towards the creation of future superconducting quantum electronic devices.

Numerical quantum clock simulations for measuring tunneling times - Suzuki, Fumika; Unruh, William G. (Physical Review A)
We numerically study two methods of measuring tunneling times using a quantum clock. In the conventional method using the Larmor clock, we show that the Larmor tunneling time can be shorter for higher tunneling barriers. In the second method, we study the probability of a spin-flip of a particle when it is transmitted through a potential barrier including a spatially rotating field interacting with its spin. According to the adiabatic theorem, the probability depends on the velocity of the particle inside the barrier. It is numerically observed that the probability increases for higher barriers, which is consistent with the result obtained by the Larmor clock. By comparing outcomes for different initial spin states, we suggest that one of the main causes of the apparent decrease in the tunneling time can be the filtering effect occurring at the end of the barrier.